Wuzi-Yanzong-Wan inhibits testicular mitochondrial apoptosis in rats by downregulating TAp73-Mediated P38 MAPK-ADAM17 pathway - Liu, Ziao; Ni, Xiaohan; Li, Jingya; Pan, Min; Xu, Fengqing; Zhao, Hongsu; Li, Li; Wang, Tongsheng (Frontiers in Pharmacology, 2025)
ObjectiveThis study investigates the relationship between TAp73 protein overexpression and sperm quality, and evaluates the prophylactic and therapeutic effects of Wuzi-Yanzong-Wan (WZYZW) on oligoasthenospermia (OA) induced by tripterygium glycosides (TGs) and etoposide in rats. Furthermore, it elucidates the underlying mechanism by analyzing the intervention’s role in downregulating TAp73 protein expression and modulating the P38 MAPK-ADAM17 signaling pathway, ultimately providing empirical evidence to support its clinical application.MethodsSprague-Dawley (SD) rats received TGs (40 mg/kg/d for 8 weeks) to induce OA. Intervention groups were treated with either WZYZW (1 or 2 g/kg/d) or Shengjing Capsule (SJJN). Meanwhile, a TAp73-overexpressing Sertoli-germ cell co-culture system was established using etoposide (200 μM for 48 h) and treated with WZYZW-containing serum (2.5%–10%), to explore the mechanisms associated with TAp73.ResultsThe in vivo experimental results demonstrated that WZYZW treatment significantly ameliorated testicular atrophy in model rats, evidenced by increased testicular volume and elevated testicular/epididymal indices. Simultaneously, WZYZW effectively reversed sperm quality impairment in the model group, manifesting as significantly increased sperm density, enhanced sperm motility, and reduced sperm abnormality rate. Furthermore, WZYZW treatment significantly upregulated serum levels of key sex hormones (e.g., testosterone, follicle-stimulating hormone, luteinizing hormone). Mechanistic investigations revealed that WZYZW markedly suppressed germ cell apoptosis (flow cytometry confirmed a significant decrease in apoptotic cell proportion) and attenuated DNA damage (indicated by significantly reduced γ-H2AX (a DNA damage marker) fluorescence intensity). WZYZW effectively restored impaired mitochondrial function and suppressed the expression of key proteins in the mitochondrial apoptotic pathway (e.g., decreased Bax/Bcl-2 ratio, reduced Cyt-c release, inhibited activation of Caspase-9 and Caspase-3). In vivo experimental results showed that WZYZW significantly inhibited cell apoptosis, effectively suppressed membrane potential depolarization in TAp73-overexpressing model cells, inhibited the opening of the mitochondrial permeability transition pore, and concurrently suppressed the expression of proteins associated with the mitochondrial apoptotic pathway. Collectively, these changes blocked the TAp73-p38 MAPK/ADAM17 axis-activated mitochondrial apoptotic cascade, thereby exerting its testicular protective effects.ConclusionThis study highlights that WZYZW effectively alleviates testicular DNA damage and mitochondrial apoptosis, suggesting that its mechanism may be associated with reduced TAp73 expression. These experimental findings provide a novel therapeutic target for the clinical application of WZYZW in OA treatment.